Equity and trusts - Panesar, Sukhninder (Pearson Education Limited, 2017)
Includes bibliographical references and index.; Brief contents: Introduction to equity and trusts; Creating the trust relationship; Trusts implied by law; The administration of trusts; Breach of trust and remedies; Charities and charitable trusts.